In vitro antibacterial activity of shrimp chitosan against Salmonela paratyphi and Staphylococcus aureus - Islam, Md Monarul; Masum, Shah Md; Mahbub, Khandaker Rayhan (Journal of the Bangladesh Chemical Society, 2012)
Antimicrobial properties of chitosan extracted from indigenous shrimp processing waste were determined against one gram-negative (Salmonella Paratyphi) and one gram-positive bacterium (Staphylococcus aureus) in vitro. The antimicrobial activities of chitosan were explored by calculation of the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) in media supplemented with 128, 138, 168, 192, 240, 288, 300 and 320 ppm chitosan solution adjusted to pH 6 or 7. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the prepared chitosan was 288 and 300 ppm for both bacterial strains. These results indicate that chitosan from indigenous shrimp processing waste could be used as an effective antibacterial agent in the food industry. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9707 Journal of Bangladesh Chemical Society, Vol. 24(2), 185-190, 2011